Review Article: Exploring the Impact of Human Metapneumovirus: A Red Global Alarm for 2025 - Asaad Abbas ALadlaan; Nuha Jabori Hadi; Ali Mohammed Barakat (مجلة علوم ذي قار)
Respiratory infections including Respiratory syncytial virus (RSV) and Human metapneumovirus (hMPV) are the most common worldwide   infections, Respiratory syncytial virus’s (RSV) and  hMPV considers a public health concern among all countries since they are sharing same clinical presentation, these viruses have the potential to unleash as the global pandemic has already laid a strong foundation. While the similarities with RSV are clear,  patient needs to follow  a  concrete approach including continuous administration of antibiotics or antivirals to fight these viruses. Mild to severe complications with hMPV demand more research covering both hMPV and RSV concurrently. This review attempts to improve knowledge of the pathogen and frequency of hMPV as a possible transmission vector by aggregating present data. Examining its possible effects and clinical differences among the human population will also help us to better understand  hMPV and suggest ways of prevention. In conclusion, we seek to emphasize findings from prior research while generating empirical evidence to support our claims. Moreover, it is anticipated that by 2025, hMPV may present a global health risk.